Towards the development of digital storytelling practices for use in resource-poor environments, across disciplines and with students from diverse backgrounds - Gachago, Daniela; Ivala, Eunice; Barnes, Veronica; Penny Gill, Penny Gill; Felix-Minnaar, Joseline; Morkel, Jolanda; Vajat, Nazma (South African Journal of Higher Education, 2016)
Digital storytelling has entered Higher Education as a pedagogical tool for enhancing students digital literacies in digitally saturated contexts. Increasing access to freely available software programs for video production and the ubiquity of mobile technologies have made digital storytelling viable in resource-poor environments. This paper reports on an on-going project at a university of technology in South Africa employing both quantitative and qualitative research approaches, with the aim of understanding students perceptions of context-specific digital storytelling practices across various disciplines and student backgrounds. Pierre Bourdieus notions of field, habitus and capital as well as Tara Yossos community cultural wealth were applied to understand students perceptions of practices of digital storytelling that emerged from this project. We argue that complex technology projects, such as digital storytelling, are potentially viable in poorly-resourced environments, across disciplines and with students with diverse digital literacies and backgrounds, provided that: 1. technical barriers are lowered to the minimum and technologies are adopted that are freely available, owned by or easily accessible to students, 2. that the appropriate model is chosen based on these students social and cultural capital, and 3. that the community cultural wealth of students is considered in curriculum delivery.